PEMAHAMAN BAHASA: TELAAH KONSEPTUAL TENTANG DEFENISI DAN CIRI-CIRI BAHASA INDONESIA - Melisha Ayudia; Ayu Hazri Yani; Putri; Silvina Noviyanti; Azizah Nurfadilah (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Language is the primary means of communication used by humans to convey ideas, thoughts, and feelings in social life. In the Indonesian context, the Indonesian language plays an important role as both the national language and the official state language, functioning as a unifying tool for a society with diverse cultural backgrounds and regional languages. This study aims to conceptually examine the definition of language and the characteristics of the Indonesian language from a linguistic perspective. The research method employed is a qualitative approach using a library research design through the analysis of various relevant scientific literature sources. The results of the study indicate that the Indonesian language possesses several main characteristics: it is systematic, arbitrary, productive, dynamic, and conventional. These characteristics demonstrate that Indonesian is a structured linguistic system capable of developing in accordance with the communication needs of society. Therefore, understanding the concepts and characteristics of the Indonesian language is essential to support proper and correct language use in various fields of life, particularly in education and academic communication.